Democracy, Support for Democracy and Corruption. A Longitudinal Study of Latin American Countries - Davide Grassi (Coordinamento SIBA, 2017)
Although often unable to satisfactorily solve the problem, democracy (especially enduring democracy) is commonly believed to reduce corruption. Yet, both Transparency International and the World Bank continue to attach a high risk of corruption to Latin American countries: corruption and impunity remain prevalent in the area, despite consolidating democratic regimes and recent anticorruption reforms. Using level of democracy and its endurance, as well as information on the perceptions of democratic performance and corruption obtained from the Latinobarometro, we analyzed a panel data covering the period 2005-2010 in 14 Latin American countries. Our main results show that levels of democracy and citizens' assessment of government fairness have a positive impact on corruption. However, satisfaction towards democracy has the opposite effect: when citizens believed democratic governments and public administrations to be efficient, they also perceived that gains against corruption had significantly decreased.